EVALUATION OF PASSENGER CAR EQUIVALENT (PCE) ON STRAIGHT MOVEMENTS AND TURN TO THE RIGHT MOVES (CASE STUDY: FOUR SIGNAL INTERSECTION AT CITY OF BANDUNG) - Suri Widyatami, Filki
Until now, the manual calculation of traffic road in Indonesia is still based on document called Manual of Road Capacity (MKJI) which has been compiled since 1997. Due to the road traffic condition that changes by the time, there is evaluation needed to check the PCE score mostly on motorcycle and heavy vehicle, whether the score is still relevant to be used in current condition or not. Therefore, the purposes of this thesis are to: 2) Determine the PCE score of motorcycle (MC) and heavy vehicle (HV) on straight moves and turn to the right moves in four signal intersection, 2) Analyze the comparison between saturated flow score based on the survey and MKJI method and Akcelik method, 3) Analyze the PCE score based on calculation and PCE score taken from MKJI, reviewing the feasibility PCE of MKJI with current traffic conditions 4) To know the relation of proportion-relationship motorcycle and heavy vehicle with PCE score.